Grey matter atrophy in prodromal stage of dementia with Lewy bodies and Alzheimer's disease. Issue 1 (December 2016) - Blanc, Frederic; Colloby, Sean; Cretin, Benjamin; de Sousa, Paulo; Demuynck, Catherine; O'Brien, John; Martin-Hunyadi, Catherine; McKeith, Ian; Philippi, Nathalie; Taylor, John-Paul
Abstract Background Little is known about the patterns of brain atrophy in prodromal dementia with Lewy bodies (pro-DLB). Methods In this study, we used SPM8 with diffeomorphic anatomical registration through exponentiated lie algebra to measure grey matter (GM) volume and investigate patterns of GM atrophy in pro-DLB (n = 28) and prodromal Alzheimer's disease (pro-AD) (n = 27) and compared and contrasted them with those in elderly control subjects (n = 33) (P ≤ 0.05 corrected for family-wise error). Results Patients with pro-DLB showed diminished GM volumes of bilateral insulae and right anterior cingulate cortex compared with control subjects. Comparison of GM volume between patients with pro-AD and control subjects showed a more extensive pattern, with volume reductions in temporal (hippocampi and superior and middle gyri), parietal and frontal structures in the former. Direct comparison of prodromal groups suggested that more atrophy was evident in the parietal lobes of patients with pro-AD than patients with pro-DLB. In patients with pro-DLB, we found that visual hallucinations were associated with relative atrophy of the left cuneus. Conclusions Atrophy in pro-DLB involves the insulae and anterior cingulate cortex, regions rich in von Economo neurons, which we speculate may contribute to the early clinical phenotype of pro-DLB.